Alat bantu pembentukan kurikulum institusi pengajian tinggi, kajian kes fakulti sains komputer dan sistem maklumat, UTM - Palaraman, Robiahtuladawiah (2006)
Toolkit for development of curriculum in higher education institutes. Case study : Fakulti Sains Komputer dan Sistem Maklumat, UTM. This system will develop to aid lecturers in creating a curriculum. Having this toolkit would promise an easier way to prepare the new curriculum. Codification of knowledge and information will be done to underline the guidelines to create the new curriculum parallel to the vision, objective, learning content to produce a learning output, course and program that fulfills the specifications or criteria gives by the authority, clients, stakeholder and also constitution party. This toolkit would enhance the interaction between the lecturers and the head departments and the committee as a whole. The toolkit was developed using the prototype methodology and database using the Microsoft Access 2000 and interface using Active Server Pages (ASP).